A conceptual framework for mobile application in learning arabic language proficiency - Wan Ab Aziz Wan Daud; Wong Kung Teck; Mohammad Taufiq Abdul Ghani (2018)
Over the years, there are rapid development in complex devices and gadgets such as smartphones, tablets, PCs and laptops. Consequently, this leads to rapid development in mobile technology that has made us reliant to mobile applications in our lives. Mobile applications are becoming popular tools for education and business, as well as for entertainment and employment. This has sparked the development of innovative and interactive education applications that can be used to encourage and facilitate conducive learning. Therefore, this research is conducted to create a further understanding on the use of mobile applications to enhance learning. Here, it is believed that the use of mobile applications in education have many benefits. This is because applications enable students to visualize what being learned throughout their learning process which makes learning more effective for them. This study describes the use of an instructional design model to design and develop an application for learning Arabic language and improve its proficiency. The use of the combination of Kemp model and Gerlach & Ely model is proposed in developing the application.